The Effect of Climate Change and Extreme Weather Events on Tourism - Andrea Bigano; Alessandra Goria; Jacqueline Hamilton; Richard S.J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2005)
Tourism is an industry of primary importance for the world economy. For some countries, tourism is the first source of income and foreign currency, and many local economies heavily depend on tourism. Tourists are sensitive to climate and to climate change, which will affect the relative attractiveness of destinations and hence the motive for international tourists to leave their country of origin. Yet, until recently, the attention devoted by the tourism literature to climate change and by the climate change literature to tourism has been quite limited. This paper is divided in two parts. The first part reviews the literature on the relationship between climate change and tourism. We find that the existing studies have but started unveiling the complexities of this relationship, by means of very heterogeneous approaches and scarcely comparable studies. A comprehensive, coherent quantitative message cannot yet be drawn from the literature. The broad qualitative message is clear, however: climate change will affect tourism, and the consequences for the economy might be wide and pervasive. The second part analyses empirically the relationship between climate characteristics, weather extremes and domestic and international tourism demand across Europe, with a focus on Italy. This study draws on the results on the Italian tourist sector of the WISE project, a multi-sector research project that investigates the impacts of extreme weather events on the socio-economic systems of some European countries by means of both quantitative and qualitative analyses. In general, temperature is the strongest indicator of domestic tourism. The relationship between tourism and temperature is generally positive in the same-month all across Europe, except in winter sports regions. The climate impact depends as well on destination type: for example coastal resorts respond more favourably to summer temperature increases than inland resorts. Moreover, it is not just temperature that counts, but also the expectations about future temperature levels; not just the presence of weather extremes, but also the expectations about their future occurrence. Qualitative results, based on individual surveys, show that during an unusually hot summer day trips are more climate-responsive than short breaks, that short breaks are more climate-responsive than main holidays, and that most people tend not to change plans for their main vacation: those that do change either stay at home or in their own country. On the basis of our literature survey and of our empirical studys results, the paper concludes by indicating the most urgent gaps to be filled in the knowledge about the relationship between climate change and tourism and by pointing at the most promising directions for further research.
Keywords: L83; Q25; C23; C42; 330; Tourism; Climate change; Extreme weather events